Rates and Routes of Hysterectomy for Benign Indications in Austria 2002 – 2014 - Edler, Katharina Maria; Tamussino, Karl; Fülöp, Gerhard; Reinstadler, Evi; Neunteufel, Walter; Reif, Philipp; Laky, Rene; Aigmüller, Thomas (Geburtshilfe und Frauenheilkunde, 2017)
Introduction Rates and routes of hysterectomy have implications for quality, costs and training. This study analyzed rates of benign hysterectomy and surgical approaches for benign hysterectomy in Austria from 2002 to 2014. Material and Methods This was a population-based retrospective observational study of coding data from all acute care hospitals (public and private) in Austria. Main outcome measures were numbers of women undergoing hysterectomy for benign indications in Austria per year and the route of hysterectomy for benign indications. Results The number of benign hysterectomies performed per year declined from 10 675 in 2002 to 7747 in 2014, a decline of 27%. The use of vaginal hysterectomy was stable (53% and 47%, respectively). Use of laparoscopic techniques increased (5% in 2002, 32% in 2014) whereas use of abdominal hysterectomy decreased (41% and 20%, respectively). Conclusions Numbers of benign hysterectomies performed per year in Austria declined substantially between 2002 and 2014. Use of vaginal hysterectomy was stable at about 50%, whereas increased use of laparoscopic techniques was associated with lower rates of open hysterectomy.
Keywords: hysterectomy; hysterectomy rates; routes of hysterectomy; vaginal hysterectomy; minimally invasive hysterectomy; abdominal hysterectomy